The Clinical Presentation of Early-Onset Psychotic Disorders: A Descriptive Study in Child and Adolescent Inpatient Setting - Pervaiz, Zainab; Azhar, Masood; Asghar, Hafiz Sohaib; Bilal, Muhammad Arslan; Imran, Nazish (Journal of Pakistan Psychiatric Society, 2026)
Background: Early-onset psychosis starts before the age of 18 years. It differs from the adult-onset psychosis in terms of the clinical presentation and response to the therapy. The aim of the study was to identify the common symptoms of Early Onset Psychosis and the social and educational impairment resulting from it. Methods: A retrospective study was conducted in Child and Adolescent Psychiatry Department, Mayo Hospital, Lahore to assess the clinical profile of patients diagnosed with psychotic disorders.. A proforma was designed for data extraction based on the literature review and in accordance with DSM-5 which included common presenting symptoms at admission along with other relevant clinical and demographic information. Data was collected from the inpatient file records Results: A total of 116 inpatient record files of admitted patients were included. 70% of the patients were females and the mean age at admission was 13(±1.6). Schizophrenia spectrum disorders were present in 78% of the patients and Brief Psychotic Disorder was the most common diagnosis. Symptoms including odd behavior, speech disorganization, deterioration in daily life activities, and perceptual abnormalities were the most common symptoms. Conclusion: The study provides insight into the clinical presentation and psychosocial impact of psychosis in children and adolescents. It can help in the early detection of Psychotic Disorders in this age group and in formulating a better treatment and management plan.